Comparative Evaluation of the Efficacy of ProTaper & Mtwo Rotary Retreatment System and Conventional Hand H-files for Removal of Gutta-percha from Root Canal - A Stereomicroscopic Study - Krutika D. Chudasama; Shraddha Chokshi; Zarana Sanghvi; Nishit Patel; Naman Vaidya; Deesha Chhaya (Wolters Kluwer Medknow Publications, 2024)
Background Root canal retreatment aims to eliminate or substantially reduce the microbial load from the root canal and removal of previous root filling materials is the primary goal of nonsurgical retreatment. Aim To comparatively evaluate the effectiveness of ProTaper retreatment files, Mtwo retreatment files, and Hedstrom files along with Gates Glidden (GG) Drill by using a stereomicroscope for the detection of remaining gutta-percha after root canal retreatment using a stereomicroscope. Materials and Methods Forty-five test samples were divided into three experimental groups (15 samples each), such as Group A-ProTaper retreatment files; Group B-Mtwo retreatment files; Group C-Hedstrom files along with Gates Glidden Drill. After routine endodontic treatment in the test samples, gutta-percha was removed from the test samples as per the division of different retreatment file systems. Further, test samples were divided longitudinally and were evaluated under the stereomicroscope. Stereomicroscopic images were captured and analysed under Image Analyser Software-Image J. Statistical Analysis One-way ANOVA test was used for comparison of gutta-percha removal between the groups and Tukey's post hoc test was used for pairwise comparisons. Results The least remaining filling material was seen in specimens retreated with the ProTaper universal system. The highest remaining filling material was seen in specimens retreated with Hedstrom file with Gates Glidden Drill. Conclusion All experimental test techniques left gutta-percha remnants within the root canal. ProTaper universal rotary retreatment system proved to be an efficient method of removing gutta-percha and left relatively less volume in comparison with other test systems.